Study of Local Curriculum Implementation Imparting Local Scientific Knowledge in Nepal - Gem Prasad Gurung; Dilu Ram Parajuli (International Journal of Innovation and Education Research, 2021)
This study focuses on the status of local curriculum development and implementation with imparting scientific knowledge in Purvakhola, Palpa. Though the education policy of Nepal is authorizing the construction of the local curriculum and its implementation, due to different causes most school clusters are not showing interest in the local curriculum. So, the study explores an existing gap in the educational policy of the government of Nepal and its implementation by local educational authorities. This study is adopting a qualitative method and data generation and its interpretation is based on primary data. The finding is drawn on its status of implementation of local curriculum, local curriculum should be designed based on local needs and covering local scientific knowledge. Also, it should be included local heritages, local autonomy, and the policy of decentralization of curriculum development.